Evaluating access to psychosocial services for the medicaid-insured children in Georgia - Yujia Xie; Pravara Harati; Janani Rajbhandari-Thapa; Nicoleta Serban (BMC Public Health)
Abstract Background Evaluating access to psychosocial services can inform policy decision-making on ways to address shortages in the availability of mental health (MH)-specialized providers. The objective of the study was to assess how the mental health (MH)-specialized workforce met the demand for psychosocial services of Medicaid-insured children in Georgia, with direct relevance in establishing quantitative network adequacy. Methods We used the 2018 Medicaid (TAF) claims data, the 2018 National Plan and Provider Enumeration System database, and the 2019 Georgia school-based program data to estimate community-level demand and practice-level supply of psychosocial services. We evaluated the availability of services using mathematical models. The outcome measures were met demand and travel distance. We explored the impact of increasing in-home care delivery, expanding Medicaid participation, or increasing caseload for the Medicaid-participating providers on improving met demand for psychosocial services. Results Our findings showed that 34% of the demand from Medicaid-insured children in Georgia remained unmet, and 25% of the Georgia census tracts (rural 79%; urban 16%) had < 50% service coverage. The travel distance for in-clinic services was 3.84 miles on average. Increasing provider Medicaid caseload or expanding Medicaid participation, resulting in a 5–40% supply increase, would reduce unmet demand to 7% and decrease the number of unserved and underserved census tracts to 3% and 2% respectively. Meeting 75% of the demand required a 15% increase in the supply. Conclusions The main source of network inadequacy was the scarcity of MH providers available to Medicaid-insured children in Georgia, coming from both the limited caseload of existing MH providers and low Medicaid participation, rather than travel constraints. Increasing provider caseload and expanding Medicaid participation were found to reduce unmet demand. Interventions increasing caseloads were the most effective intervention since existing Medicaid-participating providers already had sufficient network coverage geographically.